Outcomes of cystocele repair surgery in relation to different anesthesia methods - Pakbaz, Mojgan; Mogren, Ingrid; Löfgren, Mats (Acta obstetricia et gynecologica Scandinavica, 2010)
Abstract Objective. To investigate outcomes of cystocele surgery by different anesthesia and evaluation of patient satisfaction. Design. Population-based, retrospective study. Setting. All clinics that included patients in the Swedish National Register for Gynecological Surgery. Population. A total of 1,364 women who underwent cystocele repair from January 2006 to June 2009. Methods. The study population was retrieved from the Register among women who had surgery and where there was complete information on concurrently used anesthesia. Clinical variables were compared. Peri- and postoperative complications were investigated. Multivariate logistic regression analysis was applied to identify independent factors for patient satisfaction. Main outcome measures. Time to recovery, complications and patient satisfaction. Results. We found a wide variation between hospitals with respect to use of local anesthesia (LA) in cystocele surgery. Length of hospital stay, duration of use of postoperative painkilling drugs, and patient-reported time to return to daily activity were shorter in the LA group compared to the other two anesthesia forms. Postoperative complications did not differ between groups. Age (≥50 years) and patient-reported complications were independent factors related to patient satisfaction (OR 3.05; 95%CI 1.36-6.82 and OR 0.21; 95%CI 0.12-0.36, respectively). Patient satisfaction did not relate to methods of anesthesia. Conclusion. Cystocele surgery can be performed safely using LA thus limiting the use of more invasive anesthesia methods. LA benefits patients and should be increasingly used.